Theory of Turbulent Equilibrium Spheres with Power-law Linewidth–Size Relation - Sanghyuk Moon; Eve C. Ostriker (The Astrophysical Journal, 2024)
Dense cores inherit turbulent motions from the interstellar medium in which they form. As a tool for comparison to both simulations and observations, it is valuable to construct theoretical core models that can relate their internal density and velocity structure while predicting their stability to gravitational collapse. To this end, we solve the angle-averaged equations of hydrodynamics under two assumptions: (1) the system is in a quasi-steady equilibrium; (2) the velocity field consists of radial bulk motion plus isotropic turbulence, with turbulent dispersion increasing as a power law in the radius. The resulting turbulent equilibrium sphere (TES) solutions form a two-parameter family, characterized by the sonic radius r _s and the power-law index p . The TES is equivalent to a Bonnor–Ebert (BE) sphere when r _s → ∞ . The density profile in the outer regions of the TES is slightly shallower than the BE sphere, but is steeper than the logotropic model. Stability analysis shows that the TESs with size exceeding a certain critical radius are unstable to radial perturbations. The center-to-edge density contrast, mass, and radius of the marginally stable TES all increase with increasing average velocity dispersion. The FWHM of the column density profile is always smaller than the critical radius, by a larger factor at higher velocity dispersion, suggesting that observations need to probe beyond the FWHM to capture the full extent of turbulent cores. When applied to the highly turbulent regime typical of cluster-forming clumps, the critical mass and radius of the TES intriguingly resembles the typical mass and radius of observed star clusters.